Epigenetic Alterations in Prenatal Stress Mice as an Endophenotype Model for Schizophrenia: Role of Metabotropic Glutamate 2/3 Receptors - Matrisciano, Francesco; Dong, Erbo; Nicoletti, Ferdinando; Guidotti, Alessandro (Frontiers in Molecular Neuroscience, 2018)
Mice subjected to prenatal restraint stress (PRS mice) showed biochemical and behavioral abnormalities consistent with a schizophrenia-like phenotype (Matrisciano et al., 2016). PRS mice are characterized by increased DNA-methyltransferase 1 (DNMT1) and ten-eleven methylcytosine dioxygenase 1 (TET1) expression levels and exhibit an enrichment of 5-methylcytosine (5MC) and 5-hydroxymethylcytosine (5HMC) at neocortical GABAergic and glutamatergic gene promoters. Activation of group II metabotropic glutamate receptors (mGlu2 and -3 receptors) showed a potential epigenetically-induced antipsychotic activity by reversing the molecular and behavioral changes observed in PRS mice. This effect was most likely caused by the increase in the expression of growth arrest and DNA damage 45-β (Gadd45-β) protein, a molecular player of DNA demethylation, induced by the activation of mGlu2/3 receptors. This effect was mimicked by clozapine and valproate but not by haloperidol. Treatment with the selective mGlu2/3 receptors agonist LY379268 also increased the amount of Gadd45-β bound to specific promoter regions of reelin, BDNF, and GAD67. A meta-analysis of several clinical trials showed that treatment with an orthosteric mGlu2/3 receptor agonist improved both positive and negative symptoms of schizophrenia, but only in patients who were early-in-disease and had not been treated with atypical antipsychotic drugs (Kinon et al., 2015). Our findings show that PRS mice are valuable model for the study of epigenetic mechanisms involved in the pathogenesis of schizophrenia and support the hypothesis that pharmacological modulation of mGlu2/3 receptors could impact the early phase of schizophrenia and related neurodevelopmental disorders by regulating epigenetic processes that lie at the core of the disorders.